Making Sibling Teams Work The Next Generation - Aronoff, C. (A Family Business Publication, 2011)
Through pages filled with wisdom, tips, guidelines and experiences, the authors seek to navigate brothers and sisters who work in the family business or who are active owners through the challenges and opportunities and to retain the integrity of the family while serving the business.